THE USE OF THINK BEFORE, WHILE, AFTER READING (TWA) STRATEGY TO IMPROVE STUDENTS’ READING ACHIEVEMENT - Yuni Indah Sari (Language and Education Journal, 2017)
Reading as an essential skill in order to obtain information written in the books. Therefore, students must master the skill of reading. This study aimed to find whether there was a significant difference in students’ reading achievement between the students who were taught using Think before, While, After reading (TWA) strategy and that of those who were not. The samples were the two classes of the eleventh-grade students of SMA Negeri 1 Teluk Gelam. The data obtained using the written test in which the students chose the correct answer after reading hortatory exposition texts. Then, to analyze the data, the t-test was used if the data were considered normal and homogenous. The result of t-test showed that t-obtained was 9.8 at the significance level of p<0.05 with df 58 and the critical value of t-table was 1.99 Since the value of t-obtained exceeded the critical value of t-table, the null hypothesis (Ho) was rejected and the research hypothesis (Ha) was accepted. It means that there was a significant difference in students’ reading achievement between the students who were taught using Think before, While, After reading (TWA) strategy and that of those who were not. Think before, While, After reading (TWA) strategy guided the students to find the main idea/topic of the text, specific/detail information of the text, synonym, and antonym of the vocabularies written in the text